Community Paramedics in Australia: A Case Study Adapting the Canadian Community Paramedicine at Clinic (CP@clinic) Program in Rural Australia, Using an Implementation Science Approach. - Agarwal, Gina; Mahal, Guneet; Spelten, Evelien; Hardman, Ruth; Reynolds, Louise; Heald, Simone; Hemming, Laura; Angeles, Ricardo; Marzanek, Francine; Koester, Christie; Pirrie, Melissa; Plishka, Mikayla; et al. (Journal of Primary Care & Community Health, 2026)
Objectives: Community Paramedicine (CP) is a rapidly expanding subset of paramedicine where paramedics work in primary care and community settings. The Community Paramedicine at Clinic (CP@clinic) Program, widely established in Canada, is evidenced to fill gaps and generate cost savings in the healthcare system, reduce unnecessary 911 calls, and improve patient health. Due to healthcare system demands, there was strong interest and need for an evidence-based CP program in Victoria, Australia. Methods: This study investigates the adaptation of the CP@clinic program in Australia, informed by the Institute for Healthcare Improvement's (IHI) 'Framework for Going to Full Scale'. Data was collected from meeting minutes documenting the scale-up and was thematically categorized within subsections of the IHI Framework. Results: Program scale-up began in 2022, and by 2025 was implemented in 4 sites and 35 locations, serving 676 patients. Key factors guiding the ongoing success of the scale-up included the presence of CP@clinic as existing best-practice, thorough assessment of the local context prior to implementation, building trust within the community, establishing strong communication networks, and integrating pathways for long-term sustainability. Conclusions: CP program expansions may benefit from using a guided implementation science framework, such as the IHI Framework for Going to Full Scale.